Peran Parameter Trombosit sebagai Biomarker Keparahan dan Prognosis Pasien Coronavirus Disease 2019 - Nadya Aulia Rahmadhanty; Yani Triyani (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Increased risk of mortality of Coronavirus Disease 2019 (COVID-19) patients with severe symptoms, often associated with cytokine storms. Cytokine storms can cause damage to bone marrow progenitor cells so that reduced platelet production leads to thrombocytopenia. Monitoring platelet parameters as a laboratory test that is easily available, affordable, and widely used, can also be used to monitor cytokine storms of COVID-19 patients. The aim of this study was to determine the role of platelet parameters as potential indicators of assessing the clinical degree of COVID-19 patients. The method of this study was scoping review. The databases used were PubMed, SpringerLink, and ScienceDirect with a total of 788 search results. The screening result of articles that suit the inclusion criteria were 162 articles and those that suit the eligibility criteria are reviewed as many as 6 articles. The results of the analysis of 6 articles reviewed, 5 articles showed that platelet count can assess the severity and prognosis in COVID-19 patients and 1 article shows that the Mean Platelet Volume value does not act as a good predictor for the severity of COVID-19 disease. The conclusion of this study is that platelet parameters act as biomarkers of the severity and prognosis of COVID-19 patients. Platelet count is more effective as a biomarker of the severity and prognosis of COVID-19 patients compared to Mean Platelet Volume, Plateletcrit, Platelet Distribution Width, and Platelet Large Cell Ratio. Abstrak. Peningkatan risiko mortalitas pasien Coronavirus Disease 2019 (COVID-19) dengan gejala parah, sering dikaitkan dengan adanya badai sitokin. Badai sitokin dapat menyebabkan kerusakan sel progenitor bone marrow sehingga produksi trombosit berkurang menyebabkan trombositopenia. Pemantauan parameter trombosit sebagai tes laboratorium yang mudah tersedia, terjangkau, dan banyak digunakan, dapat juga dilakukan untuk memantau badai sitokin pasien COVID-19. Tujuan penelitian ini untuk mengetahui peran parameter trombosit sebagai indikator potensial menilai derajat klinis pasien COVID-19. Penelitian ini menggunakan metode scoping review. Database yang digunakan yaitu PubMed, SpringerLink, dan ScienceDirect dengan jumlah artikel hasil pencarian sebanyak 788. Jumlah artikel yang sesuai dengan kriteria inklusi sebanyak 162 dan yang memenuhi kriteria eligibility direview sebanyak 6 artikel. Hasil analisis 6 artikel yang di-review, 5 artikel menunjukkan bahwa hitung jumlah trombosit dapat menilai tingkat keparahan dan prognosis pada pasien COVID-19 serta 1 artikel menunjukkan bahwa nilai Mean Platelet Volume tidak berperan sebagai prediktor yang baik untuk tingkat keparahan penyakit COVID-19. Kesimpulan penelitian ini adalah parameter trombosit berperan sebagai biomarker keparahan dan prognosis pasien COVID-19. Hitung jumlah trombosit lebih efektif berperan sebagai biomarker keparahan dan prognosis pasien COVID-19 dibanding dengan Mean Platelet Volume, Plateletcrit, Platelet Distribution Width, dan Platelet Large Cell Ratio.